Inflammasomes during SARS-CoV-2 infection and development of their corresponding inhibitors - Diarimalala, Rominah Onintsoa; Wei, Yanhong; Hu, Da; Hu, Kanghong (Frontiers in Cellular and Infection Microbiology, 2023)
Corona Virus Disease 2019 (COVID-19) continues to be a burden for human health since its outbreak in Wuhan, China in December 2019. Recently, the emergence of new variants of concerns (VOCs) is challenging for vaccines and drugs efficiency. In severe cases, SARS-CoV-2 provokes inappropriate hyperinflammatory immune responses leading to acute respiratory distress syndrome (ARDS) and even death. This process is regulated by inflammasomes which are activated after binding of the viral spike (S) protein to cellular angiotensin-converting enzyme 2 (ACE2) receptor and triggers innate immune responses. Therefore, the formation of “cytokines storm” leads to tissue damage and organ failure. NOD-like receptor family pyrin domain containing 3 (NLRP3) is the best studied inflammasome known to be activated during SARS-CoV-2 infection. However, some studies suggest that SARS-CoV-2 infection is associated with other inflammasomes as well; such as NLRP1, absent in melanoma-2 (AIM-2), caspase-4 and -8 which were mostly found during dsRNA virus or bacteria infection. Multiple inflammasome inhibitors that exist for other non-infectious diseases have the potential to be used to treat severe SARS-CoV-2 complications. Some of them have showed quite encouraging results during pre- and clinical trials. Nevertheless, further studies are in need for the understanding and targeting of SARS-Cov-2-induced inflammasomes; mostly an update of its role during the new VOCs infection is necessary. Hence, this review highlights all reported inflammasomes involved in SARS-CoV-2 infection and their potential inhibitors including NLRP3- and Gasdermin D (GSDMD)-inhibitors. Further strategies such as immunomodulators and siRNA are also discussed. As highly related to COVID-19 severe cases, developing inflammasome inhibitors holds a promise to treat severe COVID-19 syndrome effectively and reduce mortality.